Exchange of short-chain oxygenated volatile organic compounds (VOCs) between plants and the atmosphere: A compilation of field and laboratory studies (Journal of Atmospheric Chemistry, 2001)
Field and laboratory investigations of the exchange of the short-chain organic acids – formic acid and acetic acid – as well as their homologous aldehydes are discussed. Both acids are substantially released from several plant species. Emission measurements under ﬁeld conditions are compiled to give an overview of three years of measurements. Emission rates from several tree species were found in the range between zero and 60 nmoles m−2 min−1 for acetic acid and between zero and 90 nmoles m−2 min−1 for formic acid though also a deposition has been observed to orange trees. Investigations under laboratory conditions showed an order of magnitude lower emission rates with signiﬁcant differences under light and dark conditions, and a deposition was observed under certain conditions. Hence, low emission rates or even a bi-directional exchange, emission as well as deposition have to be taken into account. Further differences between ﬁeld and laboratory studies are discussed considering age of trees, stress effects and a potential production of acids by photochemical conversion of precursors inside enclosures during sampling. Field data on the exchange of formand acetaldehyde show a complex behavior. We found emission as well as uptake. The bi-directional exchange is signiﬁcantly triggered by the ambient mixing ratios of both aldehyde species and exhibits a compensation point. Further studies are needed for generalization of the exchange of these and potentially also for other compounds